2006
DOI: 10.1002/chem.200600879
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Sensors for Hg2+ in Micelles: A New Approach that Transforms an ON–OFF into an OFF–ON Response as a Function of the Lipophilicity of the Receptor

Abstract: A new approach to the use of micelles in the fluorescent sensing of metal cations is proposed and applied to the case of Hg2+. We demonstrate how it is possible to transform a system from an ON–OFF to an OFF–ON sensor by changing the length of the chain used to lipophilise a ligand that resides inside TritonX‐100 micelles together with pyrene as the fluorophore. Three tetrathia‐monoaza macrocyclic ligands have been synthesised with the same ring but functionalised on the nitrogen atom with a methyl (C1‐NS4), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 54 publications
0
24
0
1
Order By: Relevance
“…Playing with the pK a of the amines and pyridines used it is possible to tune the wide of the window and its position along the pH axes. Following this approach the same group has reported other interesting results in the sensing of metal ions [84] and also in the determination of relevant chemical-physical properties of molecules such as their lipophilicity [85]. All these systems, along with others, are reviewed in a sister review in this special issue and represent and important step forward toward the general applicability of this selfassembling approach.…”
Section: Self-assembled Fluorescent Chemosensors In Aggregatesmentioning
confidence: 96%
“…Playing with the pK a of the amines and pyridines used it is possible to tune the wide of the window and its position along the pH axes. Following this approach the same group has reported other interesting results in the sensing of metal ions [84] and also in the determination of relevant chemical-physical properties of molecules such as their lipophilicity [85]. All these systems, along with others, are reviewed in a sister review in this special issue and represent and important step forward toward the general applicability of this selfassembling approach.…”
Section: Self-assembled Fluorescent Chemosensors In Aggregatesmentioning
confidence: 96%
“…12 In particular, in a non-ionic surfactant such as TX100, the observed pKa of protonated amines and pyridines is shifted to lower values, due to the poor solvation of the protonated forms inside the micellar containers and/or to the lowered H 3 O + local concentration. 13 In our paper we were able to obtain systems with the ''on'' window in the 2-5 pH range. We have also demonstrated that a certain control on the ''on'' window position may be obtained by changing the intrinsic pKa of the protonated moieties (i.e., the pKa in bulk water) by modifying the molecular structure during synthesis.…”
Section: Introductionmentioning
confidence: 95%
“…The observed trend likely depends on the different combination of opposite contributions from the solvent and from the 1,8‐naphthalimide‐containing arm. As regards the solvent, the slightly decreased hydrophilicity of the environment with respect to water is expected to depress the protonation constants . On the other hand, the 1,8‐naphthalimide‐containing arm might stabilize some of the protonated amino groups through intramolecular H bonds with the oxygen atoms of the imide moiety.…”
Section: Resultsmentioning
confidence: 99%